Neuroprotective effect of regular swimming exercise on calretinin-positive striatal neurons of Parkinsonian rats - BORACI, HATİCE; KİRAZLI, ÖZLEM; GÜLHAN, REZZAN; ŞEHİRLİ, ÜMİT SÜLEYMAN (SPRINGER, 2020)
In Parkinson's disease (PD), physical therapy is one of the mainstays of supportive treatment modalities. This study focused on the neuroprotective effect of regular exercise on striatal calretinin positive interneurons in a rat model of PD. 6-hydroxydopamine (6-OHDA) was injected unilaterally into the medial forebrain bundle of Wistar rats. 6-OHDA lesioned (Parkinsonian) and unlesioned (control) rats were divided into sedentary and exercise groups. Exercise groups had daily swimming sessions for 30 min for 6 weeks. After 6-OHDA injections, an apomorphine-induced rotation test was performed (0.05 mg/kg, subcutaneous) at the 3rd and 6th weeks. At the end of the 6th week, brains were removed following transcardiac perfusion. The brain sections were stained immunohistochemically for tyrosine hydroxylase and calretinin reactivity. The number of rotations was significantly lower in Parkinsonian exercise group compared to Parkinsonian sedentary group at the 6th week (p = 0.024) and there was significant difference between Parkisonian sedentary groups at the 3rd and 6th weeks (p < 0.002). The calretinin positive interneurons significantly increased in the Parkinsonian exercise group compared to Parkinsonian sedentary group (p = 0.0003) and control exercise group (p < 0.0001). To conclude, the swimming exercise led to a striking increment of calretinin positive interneurons in the striatum of Parkinsonian rat. These findings indicated that the neuroprotective mechanism of exercise increased the number of striatal calretinin positive interneurons that might generate new approaches for the mechanism of neuroprotection. We concluded that striatal calretinin positive interneurons have an important role in the neuroprotective mechanisms of exercise in PD.
Keywords: Calretinin; Parkinson's disease; Rat; Striatum; Swimming exercise; TREADMILL EXERCISE; DIABETIC-RATS; GABAERGIC INTERNEURONS; GROWTH-FACTOR; EXPRESSION; MODEL; CALCIUM; DISEASE; MOTOR; ORGANIZATION